Trends in primary percutaneous coronary intervention for the treatment of acute coronary ST-elevation myocardial infarction in Latin American countries: insights from the CECI consortium - Rodriguez-Granillo, Alfredo Matías; Solórzano, Leonardo; Pérez-Omaña, Gilberto Vladimir; Ascarrunz, Diego; Pavlovsky, Hernán; Gomez-Valerio, Reynaldo; Bertrán, Ignacio; Flores, Federico; Parra, Julio; Guiroy, Juan; Mieres, Juan; Carvajal, Francisco; et al. (Frontiers in Cardiovascular Medicine, 2024)
This is a multi-center, multi-national prospective registry of patients undergoing primary Percutaneous Coronary Interventions (pPCI) in Latin America for ST-elevation Acute Myocardial Infarction (STEMI/LATAMI Registry). The study was conducted in 5 countries: Argentina, Ecuador, Venezuela, Bolivia, and the Dominican Republic, spanning from June 2021 to June 2023. All interventionalists involved in the study were originally trained at the same institution, Centro de Estudios en Cardiología Intervencionista (CECI), in Buenos Aires, Argentina. The primary objective was to evaluate procedural and in-hospital outcomes of pPCI in STEMI and in-hospital outcome in the LATAM region. Secondary endpoints included analyzing subgroups: differences between pPCI vs. pharmaco-invasive or late presenters, gender disparities, outcomes for elderly and very elderly patients, cardiogenic shock outcomes, and causes of STEMI. A total of 744 STEMI patients who underwent PCI between June 2021 and June 2023 across 5 countries and 9 centers were included. Of these, 76.3% underwent pPCI, 8.1% received pharmaco-invasive PCI, and 15.6% had late STEMI PCI. The overall in-hospital mortality rate was 2.2%. No significant differences were observed between regions when evaluating in-hospital and 30-day mortality rates. The procedural success rate was 96.2%. For the pPCI subgroup, the symptom onset-to-balloon time averaged 295.3 +/-246 minutes, while the door-to-balloon time was 55.8 +/-49.9 minutes. Femoral approach was utilized in 60.5% of cases. In 3.0% of patients, left main disease was identified as the culprit artery. On average, patients received 1.63 +/-1.00 stents each (564 drug-eluting stents and 652 bare metal stents), with 34 patients receiving only POBA. Definitive stent thrombosis was associated with the infarct artery as the primary cause of STEMI in 7.5% of patients. The utilization of assistant mechanical devices remained low at 2.1% within the pPCI group. Notably, women were older, with a significant number falling into the very elderly category (90 or older). They also exhibited higher mortality rates and a greater incidence of spontaneous coronary dissection (p<0.001, <0.001, p<0.001, p<0.003, respectively). In suitable LATAM centers, this prospective registry demonstrated that in patients with STEMI, PCI performed by well-trained operators yields outcomes comparable to those reported in more developed nations.